Analysis of factors affecting poverty in districts and cities in West Java - Basuki, Agus Tri; Nengsih , Widiya (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Poverty is a major problem facing every country. Various causes of poverty are the results of uneven development, narrow employment, low human resources, and high prices of necessities. This study aims to analyze the effect of Investment, Gross Regional Domestic Product, Government Expenditure, and Inflation on the poor in West Java province. The study used a sample size of 189 samples, consisting of 27 regencies and cities in West Java and 9 years of observation from 2014 to 2022. This study used a panel regression analysis tool. The results showed that investment and inflation had no influence on the poor in the districts / cities of West Java province from 2014 to 2022. While GRDP has a positive and significant effect on the number of poor people, while government spending has a negative and significant effect on the number of poor people in the districts / cities of West Java province from 2014 to 2022.